A Statistical Approach to Test Technical Trading Rules - Zhang, Yang (2010)
The arguments for the validation of various technical trading rules have never stopped. It appears that different results and conclusions were made from academics and market practitioners. Some studies indicated that those differences were due to different approaches that researchers performed in the studies. Quiet a number of these approaches were not proper thus could easily lead biased results. This paper employs a more sophisticated approach to test one of the most recent technical trading rules, simple moving average timing strategy, developed by Faber (2006, 2009). We employ an APARCH model to fit our sample data, which are the FTSE 100 index weekly returns from 1984 to 2010, and process Monte-Carlo simulations to create 10,000 possible paths. We then compared some risk measures obtained from those simulated time series for both Faber’s timing strategy and buy-and-hold strategy. Our results shows that Faber’s timing strategy cannot consistently outperform the market.